HEAT SHOCK PROTEINS IN AUTOIMMUNE DISEASES - Raška, Milan; Weigl, Evžen (Biomedical papers, 2005)
Heat shock proteins (hsp's) are among the most conserved proteins in evolution. They have been identified as important pathogen-related antigens as well as autoantigens suitable for construction of novel vaccines. The high evolutionary homology of hsp's has raised the question about the safety of such vaccines. Experimental and clinical observations have confirmed that hsp proteins are involved in the regulation of some autoimmune disease such as autoimmune arthritis, type 1 diabetes mellitus, atherosclerosis, multiple sclerosis, and other autoimmune reactions. It has been shown in experimental animals that some hsp proteins (especially hsp60, hsp70, and hsp10) can either induce or prevent autoimmune reactions depending on the circumstances. This article discusses the involvement of hsp proteins in the etiology of autoimmune diseases and it presents promising experimental data on the effects of immunization with hsp proteins in the prevention and therapy of autoimmune diseases.
Keywords: Heat shock protein/Autoimmunity/Hsp-immunization